A relação forma e conteúdo dos nexos conceituais de contagem em aulas online para crianças de 1º ano do ensino fundamental - Pereira, Patrícia (Universidade Federal de São Carlos, 2022)
This present research of a typically historical bibliographic-documentary qualitative nature had as theoretical and methodological foundation the historical-dialectical materialist paradigm and was conducted by the following question: "What relationship between form and content is explained in online classes for children of the 1st year of elementary school who present the conceptual concepts of counting? The objective of this study is to analyze the relationship between the form and content of the conceptual index letters (numerical sense, one-on-one correspondence, sequence/ordering, grouping) presented in online classes for children in the 1st year of elementary school. The thesis defended was that the relationship between form and content of the conceptual links of the count directly implies the relationship between teaching and learning. For the construction of the information we attended and analyzed 37 online mathematics classes transmitted by CMSPi (35.92%) of out a total of 103, during the pandemic, for children enrolled in the initial grades, elementary school in the State network of São Paulo, in the period from 27/04/2020 to 29/10/2020, in order to understand how and what conceptual connection of counting are presented, identifying the relationship form and content of these issues. The results presented showed that counting cones were addressed in online classes: one-on-one correspondence, grouping/ordering and sequence, through challenges and use of manipulated concrete material such as tampons and toothpicks. Considering the definition of numerical sense this point was not addressed in any of the online classes analyzed. In relation to the contents addressed in the classes, there is the prevalence of numerical representation in the decimal base, which is immediately indicated, after the children make use of the correspondence one by one when they are faced with the control of quantitative movements. This form of control is called counting by teachers who organize and present online classes. In this sense, we found that online classes prioritized the form through the use of manipulateable concrete materials, such as tampons, chips and toothpicks, with emphasis on the perceptible elements of the concept that manifest themselves in the colors of objects and numerical representations. The concept of counting is restricted to the indication by children of the objects from the correspondence one by one with the little fingers and immediately, they must represent the quantities by the numerical symbols that are presented in the numerical basis ten. Number is synonymous with numeral. Content is synonymous with form. The idea of quantity becomes synonymous with the numeral that represents quantity. The zero digit is not treated. Children are not known that the zero digit is a placekeeper and that numerical base 10 is positional because it consists of regular groupings.
The form and content relationship of the conceptual contents of counting in online classes for children of 1st year of elementary school
Keywords: Forma e conteúdo; Nexos conceituais de contagem; Aulas online; Conceptual linkcount; Conceptual counting issues; Online classes; CIENCIAS HUMANAS::EDUCACAO